2013
DOI: 10.1002/bip.22420
|View full text |Cite
|
Sign up to set email alerts
|

De novo design of functional proteins: Toward artificial hydrogenases

Abstract: Over the last 25 years, de novo design has proven to be a valid approach to generate novel, well-folded proteins, and most recently, functional proteins. In response to societal needs, this approach is been used increasingly to design functional proteins developed with an eye toward sustainable fuel production. This review surveys recent examples of bioinspired de novo designed peptide based catalysts, focusing in particular on artificial hydrogenases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 187 publications
(402 reference statements)
1
18
0
Order By: Relevance
“…Their oxygen sensitivity and production costs call for the development of artificial hydrogenases. Several artificial hydrogenases rely on the incorporation of artificial metal cofactors in host proteins (cytochrome c , rubredoxin, ferredoxin) or linking to a polypeptide . In the past decade, the biotin‐streptavidin technology has found widespread use for the assembly of artificial metalloenzymes (ArM) .…”
Section: Introductionmentioning
confidence: 99%
“…Their oxygen sensitivity and production costs call for the development of artificial hydrogenases. Several artificial hydrogenases rely on the incorporation of artificial metal cofactors in host proteins (cytochrome c , rubredoxin, ferredoxin) or linking to a polypeptide . In the past decade, the biotin‐streptavidin technology has found widespread use for the assembly of artificial metalloenzymes (ArM) .…”
Section: Introductionmentioning
confidence: 99%
“…Iron‐sulfur clusters are one of the primitive prosthetic groups found in extant proteins; their chemical properties, such as oxygen sensitivity often paired with low redox potentials, suggest that they originally emerged in a prephotosynthetic world . Because of their ancient origins, [FeS] clusters are widespread in nature and exhibit a wide variety of functions, ranging from electron transfer conduits within complex proteins, diffusible electron shuttles e.g., in ferredoxins, regulation of iron levels, redox sensors, and catalysts in multielectron redox reactions . These functions are carried out by various types of clusters, including [2Fe‐2S], [3Fe‐4S], [4Fe‐4S] and higher order clusters .…”
Section: Introductionmentioning
confidence: 99%
“…De novo design offers an alternative approach to investigate these factors in simplified model proteins, and it has been used extensively over the last two decades . Recently, our group and others have developed methods to engineer iron‐sulfur binding sites in coiled coils . Using an internally domain‐swapped, dimeric three‐helix bundle as starting point we designed two proteins, DSD‐bis[4Fe‐4S] and DSD‐Fdm, and we showed that a single binding site engineered in the hydrophobic core can be replicated on each half of the protein by symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations